2009
DOI: 10.4137/bmi.s3774
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Radiation-induced Leukocyte CDKN1A mRNA in Multiple Primary Breast Cancer Patients: Potential New Marker of cancer susceptibility

Abstract: This study was designed to discover blood biomarkers of cancer susceptibility using invasive multiple (n = 21), single primary breast cancer (n = 21), and control subjects (n = 20). Heparinized whole blood was incubated at 37 °C for 2 hours after 0–10 Gy of radiation, then cell cycle arrest marker CDKN1A and apoptosis marker BBC3 mRNA were quantified. This epidemiological study was practically feasible because radiation-induced mRNA was preserved for at least 1 day whenever blood was stored at 4 °C (r2 = 0.901… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…We found a dose-dependent increase in the expression of the CDKN1A and BBC3 genes in bone marrow cells of mice irradiated with 12 C ions in the Bragg peak (Figure 3). Similar results were obtained on blood cells of humans and mice after X-and gammairradiation in vitro, ex vivo, and in vivo (Mitsuhashi et al 2009;Rezaeejam et al 2015). Mitsuhashi and colleagues (2009) observed a full similarity between the degrees of induction of CDKN1A and BBC3 mRNA expression after gamma-irradiation of human blood at doses of 0.1, 1.0, and 10 Gy.…”
Section: Discussionsupporting
confidence: 73%
“…We found a dose-dependent increase in the expression of the CDKN1A and BBC3 genes in bone marrow cells of mice irradiated with 12 C ions in the Bragg peak (Figure 3). Similar results were obtained on blood cells of humans and mice after X-and gammairradiation in vitro, ex vivo, and in vivo (Mitsuhashi et al 2009;Rezaeejam et al 2015). Mitsuhashi and colleagues (2009) observed a full similarity between the degrees of induction of CDKN1A and BBC3 mRNA expression after gamma-irradiation of human blood at doses of 0.1, 1.0, and 10 Gy.…”
Section: Discussionsupporting
confidence: 73%
“…It is supposed that the difference of testing mode, primary design of CDKN1A gene composition and application of the primaries might be responsible for the diversity of the results. For example, Mitsuhashi et al [39] reported that multiple primary applications in CDKN1A gene composition showed higher induction of CDKN1A mRNA than single primary and control groups when leukocytes from multiple primary breast cancer patients were irradiated. The difference of mouse strain in experiment, exposure and treatment methods of the sample are also factors resulting in diversity of CDKN1A mRNA results.…”
Section: Discussionmentioning
confidence: 99%
“…IFIT2 inhibits migration and proliferation in squamous cell carcinoma cultures [ 41 ]. IFIT1 was one of a small group of genes that predict carcinogenesis after training on DNA-damage response [ 40 ], while STARD13 is upregulated in human lymphocytes following gamma-irradiation [ 51 ], suggesting that IFIT1 may be a downstream target of STARD13 following DNA damage.…”
Section: Discussionmentioning
confidence: 99%